ChemInform Abstract: Acentric Polyborate, Li3[B8O12(OH)3], with a New Type of Anionic Layer and Li Atoms in the Cavities. Issue 23 (16th May 2013) - Belokoneva, Elena L.; Dimitrova, Olga V.
Abstract Single crystals of Li3[B8O12(OH)3] are obtained by hydrothermal synthesis of a mixture with a molar ratio of PbCO3:Bi2O3:LiIO3:B2 O3:SiO2 = 1:1:2:3:1 (autoclave, 270 °C, 71 bar, 18—20 d).